REPRESENTATIVES OF WOMEN 2019 LEGISLATIVE ELECTIONS IN CENTRAL JAVA INDONESIA - Riyanti, Ratna; Absori, Absori (International Journal of Psychosocial Rehabilitation, 2020)
This research began with an effort to identify the representation of women summarized in an election and realization law that is in the Central Java Provincial Parliament. As for the fact that what has been regulated in the electoral legislation from 2003 to 2017, has not been realized from the desired expectations of 30% representation of women in parliament. The issue of gender equality in Indonesia is currently an endless issue and is still being fought for at the legislative and executive levels. Increasing the representation of women in state institutions must be accompanied by an understanding of gender equality especially in policy making institutions. The results of the study that the representation of women in the General Election of members of the Central Java DPRD in 2019 did not reflect gender equality and justice, in fact there were many women who participated in politics, but there were so many obstacles and challenges faced, one of which was patriarchal culture. The low representation of women legislative members is due to the patriarchal culture that still thickens in society. This is what makes women's opportunities limited to become a member of the legislature. Women deserve to do domestic work).